Adoption of halal Korean cosmetics among Muslim students: Insights from Islamic private universities - Sudarsono, Heri; Ardiami, Kinanthi Putri; Sujono, Rusny Istiqomah; Suciningtias, Siti Aisiyah; Fitriyani, Yeni; Khasanah, Miftakhul; Ikawati, Retty; Rahmi, Asri Noer; Ash Shidiqie, Jannahar Saddam (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study aimed to analyze the purchase intentions of Muslim students from private Islamic universities in Indonesia toward halal cosmetics in Korea.Methodology – This study involved 287 Muslim students from eight private Islamic universities in Indonesia. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to examine the relationships between the variables.Findings – The results reveal that attitude, brand image, country of origin, and fear of missing out (FOMO) significantly influence purchase intention. Among these, brand image exerts the strongest effect, followed by FOMO, whereas country of origin has a smaller influence. In contrast, halal knowledge and religiosity do not directly affect purchase intention, although they significantly influence attitudes.Implication – These findings underscore the importance of Korean halal cosmetic brands in building strong brand image and fostering positive consumer attitudes. Companies should focus on the perceived product quality, innovation, and alignment with values that are important to Muslim consumers. In addition, the significant role of FOMO suggests the effectiveness of marketing strategies that create urgency and exclusivity.Originality – This research is original in its focus on Korean halal cosmetic purchase intentions among Muslim students from eight Islamic private universities in Indonesia. It contributes to the understanding of how brand image, religiosity, halal knowledge, country of origin, and FOMO shape consumer behavior in the halal cosmetic market.